(untitled) (Research, Society and Development, 2025)
Oral cancer is one of the main neoplasms that affect individuals worldwide, and is increasingly present in the young adult population. This study aimed to analyze the development of oral cancer in young patients. An integrative review of the literature was carried out using the PubMed, LILACS and Google Scholar databases, including articles published between 2015 and 2025, in Portuguese and English, available in full. It can be concluded that SCC is much more aggressive when diagnosed in young patients and that the age range of the disease is increasingly decreasing, which raises an alert for the habits that are making adolescents and young adults susceptible to developing SCC, without neglecting the genetic factors involved in some cases of the disease.